2021
DOI: 10.1080/2331186x.2021.1977106
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting university image among undergraduate students: the case study of qatar university

Abstract: Worldwide there is an increase in competition between higher education institutions seeking to ascertain their position in the world ranking, resulting in universities introspectively reflecting on their image and student satisfaction. This is especially the case in the Gulf Cooperation Countries, where there has been significant growth in higher education institutions. This study examines the factors that influence Qatar University's image among undergraduate students and predicts factors impacting students' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 91 publications
3
12
0
Order By: Relevance
“…Regarding gender, these findings indicated that male graduate alumni reported a more positive view of the university's image than their female counterparts. This finding aligns with research that reported that gender influenced university image ( Al Hazaa et al., 2021 ; Clemes et al., 2013 ). However, this finding also breaks from other research findings that indicate that gender did not significantly influence graduates' image of the university ( Aghaz et al., 2015 ; Sultan and Wong, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding gender, these findings indicated that male graduate alumni reported a more positive view of the university's image than their female counterparts. This finding aligns with research that reported that gender influenced university image ( Al Hazaa et al., 2021 ; Clemes et al., 2013 ). However, this finding also breaks from other research findings that indicate that gender did not significantly influence graduates' image of the university ( Aghaz et al., 2015 ; Sultan and Wong, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…The Qatari graduate alumni have a better image of the University than the non-Qatari graduate alumni. Previous studies have reported that nationality influenced university image ( Al Hazaa et al., 2021 ; Wilkins and Huisman, 2011 , 2015 ). For example, Kazoleas et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the role of human resources and the quality of university services in university reputation, Participant 6 emphasized, "Attracting expert and efficient personnel, including distinguished professors and skilled employees, as well as admitting elite and high-quality students, and ensuring excellent university services for stakeholders, significantly impacts the university's external environment and reputation." Alhaza et al (2021), Manzoor et al (2021), and El Alfy and Abukari (2020) believe that workforce and the quality of tasks and services presents a positive image. Other researchers have highlighted the influence of various factors, including the quality of education and research, the academic standing of the university, the effectiveness of university services, and the performance of employees in their roles (Alhaza et al, 2021;Bagheri Kani and Erfanifar, 2010;El Alfy and Abukari, 2020;Ilgan et al, 2018;Lafuente-Ruiz-de-Sabando et al, 2018;Manzoor et al, 2021;Masarat and Imani, 2020;P erez-D ıaz and Rodr ıguez, 2015;Sirkeci and O'Leary, 2022;Vosoughi-Nayeri et al, 2017).…”
Section: Ijem 382mentioning
confidence: 99%
“…Alhaza et al (2021), Manzoor et al (2021), and El Alfy and Abukari (2020) believe that workforce and the quality of tasks and services presents a positive image. Other researchers have highlighted the influence of various factors, including the quality of education and research, the academic standing of the university, the effectiveness of university services, and the performance of employees in their roles (Alhaza et al, 2021;Bagheri Kani and Erfanifar, 2010;El Alfy and Abukari, 2020;Ilgan et al, 2018;Lafuente-Ruiz-de-Sabando et al, 2018;Manzoor et al, 2021;Masarat and Imani, 2020;P erez-D ıaz and Rodr ıguez, 2015;Sirkeci and O'Leary, 2022;Vosoughi-Nayeri et al, 2017). Therefore, our results regarding the quality component are consistent with the existing literature.…”
Section: Ijem 382mentioning
confidence: 99%